A study of diabetic retinopathy in diabetic foot syndrome in Western Regional Institute of India - Sipra S Engineer; Vipul K Prajapati; Nilesh J Paraskar; Kinjal Y Trivedi; Nirali P Siddhpura; Supriya H Rawat; Priyank Y Nenuji; Neha D Laspal (Asian Journal of Medical Sciences, 2024)
Background: Diabetes is a rapidly growing health challenge and potential epidemic across low-and-middle-income countries like India. Diabetic retinopathy (DR) is a consequence of diabetic microangiopathy, which may cause visual deterioration due to macular edema in any stage and vitreous hemorrhage or tractional retinal detachment in the advanced proliferative retinopathy stages. Aims and Objectives: The aim was to study the retinopathy status in diabetic patients with a risk of diabetic foot syndrome (DFS) visiting a western regional hospital in India. Materials and Methods: In this cross-sectional study, all patients with diabetes mellitus (DM) with a risk of DFS, visiting a tertiary care hospital during the study period, underwent an ophthalmological evaluation for documentation of their retinopathy status. Results: One hundred and fourteen patients diagnosed to have a risk profile for DFS were included in the study. Their mean age was 61.22 years and 81.6% were males. The mean duration of DM was 12.24 years, respectively. Of the 114 patients, 72 had DR. An increased presence of retinopathy in patients with an increased risk grade of diabetic foot (DF) was found significant by the Chi‐square test. (P<0.001). Conclusion: Our study found an increased presence of DR in Western Indian cohort with DFS. The severity of retinopathy was greater in patients with higher grades of risk for DF, therefore establishment of an association between DR and DFS will help in developing an integrated management strategy for these two grave consequences of diabetes.